Analisis Produktivitas Tenaga Kerja dengan Metode Time and Motion Study pada Proses Packing CKD dengan Variasi Cycle Time - Hadianto, Dian; Darmawan, Heru; Suwarno, Agus (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Labor productivity is one of the crucial factors in maintaining the sustainability and efficiency of the production process in manufacturing companies. This study aims to analyze labor productivity using the Time and Motion Study method in the CKD packing process at the maxi line of PT. XYZ, which has cycle time variations between product models (BRW, BKT, BDL, and BWE). The results show significant variations in work effectiveness and efficiency between models, as well as several ineffective activities such as material waiting time and outercase delays. By applying the Time and Motion Study method, this research provides recommendations in the form of cycle time evaluation, workload redistribution, and improvements in work layout and tools to enhance labor productivity.